Genome-wide assessment of the population structure and genetic diversity of four Portuguese native sheep breeds - Gaspar, Daniel; Usié, Ana; Leão, Célia; Guimarães, Sílvia; Pires, Ana Elisabete; Matos, Claudino; Ramos, António Marcos; Ginja, Catarina (Frontiers in Genetics, 2023)
As the effects of global warming become increasingly complex and difficult to manage, the conservation and sustainable use of locally adapted sheep breeds are gaining ground. Portuguese native sheep breeds are important reservoirs of genetic diversity, highly adapted to harsh environments and reared in low input production systems. Genomic data that would describe the breeds in detail and accelerate the selection of more resilient animals to be able to cope with climatic challenges are still lacking. Here, we sequenced the genomes of 37 animals from four Portuguese native sheep breeds (Campaniça, Bordaleira Serra da Estrela, Merino Branco and Merino Preto) and 19 crossbred sheep to make inferences on their genomic diversity and population structure. Mean genomic diversities were very similar across these breeds (0.30 ≤ Ho ≤ 0.34; 0.30 ≤ He ≤ 0.35; 1.7 × 10-3 ≤ π ≤ 3.1 × 10-3) and the levels of inbreeding were negligible (0.005 ≤ FIS ≤ 0.038). The Principal Components, Bayesian clustering and Treemix analyses split the Portuguese breeds in two main groups which are consistent with historical records: one comprising Campaniça and Serra da Estrela together with other European and transboundary dairy breeds; and another of the well-differentiated multi-purpose Merino and Merino-related breeds. Runs of homozygosity analyses yielded 1,690 ROH segments covering an average of 2.27 Gb across the genome in all individuals. The overall genome covered by ROH segments varied from 27,75 Mb in Serra da Estrela to 61,29 Mb in Campaniça. The phylogenetic analysis of sheep mitogenomes grouped the Portuguese native breeds within sub-haplogroup B1a along with two animals of the Akkaraman breed from Turkey. This result provides additional support to a direct influence of Southwest Asian sheep in local breeds from the Iberian Peninsula. Our study is a first step pertaining to the genomic characterization of Portuguese sheep breeds and the results emphasize the potential of genomic data as a valid tool to guide conservation efforts in locally adapted sheep breeds. In addition, the genomic data we generated can be used to identify markers for breed assignment and traceability of certified breed-products.